POLA KOMUNIKASI CIVITAS AKADEMIK DALAM RUANG VIRTUAL DI MASA ADAPTASI KEBIASAAN BARU - Anggraeni, Leni; Ramdani, alwan husni (Jurnal Sosial Humaniora, 2021)
The physical restriction policy by the Indonesian government during the COVID-19 pandemic has had significant implications for communication and information technology-based academic activities for educational institutions. The existence of interaction restrictions can inhibit the increase in the spread of the virus, but on the other hand the campus as an educational institution whose key activity is interaction must be able to adapt so that it can still carry out academic activities optimally. This study aims to examine two things in the scope of communication, namely communication patterns and communication barriers that occur within the scope of academic activities during the Enforcement of Community Activity Restrictions (PPKM). This study uses a qualitative method with case studies. To understand these communication patterns and communication barriers, we conducted in-depth interviews with the academic community of the University of Indonesia Education. The research findings show that to interact with lecturers and education staff, students can only communicate through the Learning Management System (LMS), whatsapp, and video teleconferencing. The interaction process often experiences obstacles so that it experiences misperceptions and late feedback. The conclusion of this study is that communication patterns in the academic community of the University of Indonesia Education are carried out through the medium of communication and information technology. This study also found three types of communication barriers that occur among the academic community, firstly technical barriers, secondly semantics, and thirdly psychological barriers. Further research will focus on testing the effectiveness of online learning on students’ cognitive aspects.